THE EDUCATIONAL CHALLENGES AMONG PRIVATE UNIVERSITY STUDENTS IN KLANG VALLEY AREA DURING THE PANDEMIC - Ikmal Malik; Sallehatul Asfiah; Intan Izzatul; Hardiyanti Zainuddin (fakultas Ushuluddin dan Dakwah IAIN Bone, 2021)
Currently, the world was hit by the Coronavirus disease, and it make a massive disruption for every occupation sector including education sector. The education sector no longer depends on face-to-face learning, which it shifted to online learning or known as e-learning either conducted in asynchronous or synchronous way. Thus, the implementation of e-learning is no longer an option for the Malaysian education system especially amid the pandemic crisis. However, e-learning might be boon for some students and be bane for the rest. There are many challenges that students have to face amid the pandemic. Thus, this paper examines the challenges of the students of higher learning institutions in Malaysia with the implementation of online learning during the tough situations. The data was collected by using a set of questionnaires that distributed among 113 undergraduate students at a selected university in Lembah Klang Valley area. Correlation analysis was used to test the correlation between technology literacy, self-efficacy and motivation towards e-learning. The findings indicates that all the independent variables were statistically significant towards the dependent variable.Keywords: E-Learning; Technology Literacy; Motivation; Self-Efficacy; Education; Covid-19